Symptomatic subclavian steal syndrome: Report of four Moroccan cases and literature review - El Bhali, Hajar (Int J Surg Case Rep, 2021)
INTRODUCTION: Subclavian steal syndrome (SSS) is the hemodynamic phenomenon of blood flow reversal in the vertebral artery due to significant stenosis or occlusion of the proximal ipsilateral subclavian artery. MATERIALS AND METHODS: Four patients with subclavian steal syndrome were treated in our center. Percutaneous radial approach was used for angioplasty, primary stenting of subclavian artery was performed, surgical techniques in particular carotid-subclavian bypass and carotid-subclavian transposition were used. RESULTS: We report the cases of four patients, three of which are male, with an average age of 60 years. All of them were symptomatic. Diagnosis was made by duplex ultrasound, supplemented by CT-angiography and arteriography. Endovascular treatment was attempted in all four patients, which was successful in two patients, who underwent primary stenting, and failed for the two others, for whom surgical treatment was considered. One had a subclavio-carotid bypass graft with a polytetrafluorethylene (PTFE) prosthesis and the other had a subclavio-carotid transposition. The technical results were satisfactory in all patients with symptoms resolution. The postoperative evolution was without notable complications and the postoperative checkups were satisfactory. DISCUSSION: There are excellent screening tools and effective medical therapies which can be instituted if the SSS is diagnosed early. When the need for revascularization arises, percutaneous modalities are favored given their proven long-term efficacy, decreased morbidity and mortality, and cost-effectiveness. Nevertheless, large, prospective, randomized and controlled trials are needed to compare the long-term patency rates between the endovascular and surgical techniques.